Metal modified carbon-based solid acid catalyst as well as preparation and application thereof
By using catering waste oil to prepare metal modified carbon -based solid solid acid catalysts, the problem of equipment corrosion and environmental pollution caused by traditional inorganic acid catalysts is solved, and the production of high -efficiency catalytic aldehydes (ketones) is realized. Environmental requirements.
Patent Information
- Application Number
- CN202411424103.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-24
AI Technical Summary
In the traditional acetal (ketone) industrial production methods, the use of inorganic acid as catalysts has problems such as equipment corrosion, environmental pollution and the inability to recycle the catalyst, and lacks green and environmentally friendly sustainable development solutions.
The use of catering waste oil as a raw material for carbon -based solid acids, through pre -processing methods such as ultrasound, phase metastases and heating stirring, to load the metal on the carbon material, prepare metal modified carbon -based solid acid catalysts, and in the nitrogen atmosphere atmosphere at the atmosphere of nitrogen atmosphere 剂 Burning is catalyst.
Improve the acidic nature and catalytic sites of the catalyst surface, enhance the catalytic capacity, reduce production costs, and recycle the catalyst, which is in line with the concept of sustainable development of green environmental protection.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of acetal (ketone) preparation, and in particular to a method for preparing a metal-modified carbon-based solid acid catalyst and a method for catalyzing acetal (ketone) synthesis using the catalyst. Background Art
[0002] Acetal (ketone) reaction is an important type of organic synthesis reaction, which has significant applications in food flavors, cosmetics, and pharmaceuticals. In addition, acetals can also be used as protective agents for carbonyl groups in multi-step organic synthesis.
[0003] In the traditional acetal (ketone) industrial production method, inorganic acid is often used as a catalyst. For example, the Chinese invention patent application document with publication number CN 108822236A discloses a method for preparing porous polyvinyl alcohol acetal ketone, which includes the following steps: a. Fully dissolve PVA in an aqueous solution and add a small amount of polymer chain extender to facilitate the condensation reaction and improve the degree of reaction. b. Dissolve butyraldehyde and cyclohexanone in a mass ratio of 7:3-6:4 to form a mixed solution. c. Gradient cooling of the PVA aqueous solution, first add 1 / 9 of the mixed solution, inorganic acid solution and the rest of the mixed solution in turn, and react under stirring until the product precipitates. d. After the product is alkaline stable, wash away the inorganic acid, mixed solution and PVA attached to the surface of the product. e. Place the product in a centrifuge to dry, and air dry it to porous polyvinyl alcohol acetal ketone.
[0004] Although the traditional inorganic acid method has a high yield, it is also accompanied by serious equipment corrosion, environmental protection, and the inability to recycle the catalyst. As the world's attention to environmental protection and sustainable development increases, researchers have been exploring the development of new green and environmentally friendly catalysts to overcome the uneconomical and environmentally unfriendly problems of traditional production methods. Summary of the invention
[0005] Carbon-based solid acids have shown significant advantages in the field of catalysis due to their high specific surface area and high thermal stability. Such catalysts can effectively promote the contact between reactants and catalysts and improve catalytic efficiency. With the development of green chemistry, the preparation of carbon-based solid acids using waste materials or biomass as raw materials has become a new research direction.
[0006] Waste cooking oil can usually be defined as kitchen waste, gutter oil and animal fats. The amount of waste cooking oil generated each year is huge, and its random discharge poses a serious challenge to people's health and environmental protection. This application study found that the carbonaceous material prepared using waste cooking oil has a rich hierarchical porous structure and excellent characteristics of high specific surface area, and is a type of porous carrier material with high specific surface area.
[0007] Through the research of this application, it is found that the metal-modified carbon-based solid acid prepared by loading metal on carbon material greatly improves the acidic properties of the catalyst surface, optimizes the reaction process and improves the selectivity of specific products. In addition, the combination of the two can increase the catalytic sites on the catalyst surface, enhance the catalytic ability, and reduce the amount of catalyst used while maintaining high catalytic performance, thereby reducing production costs; and the loading method helps to disperse the metal particles, avoid their aggregation, thereby extending the service life and activity of the catalyst. The catalyst and the reaction system after the reaction can be separated by filtering for secondary use, which greatly improves the efficiency of the catalyst. At the same time, using catering waste oil as a loading material for the catalyst can be harmlessly treated and resource-based, which meets the concept requirements of green environmental protection and sustainable development, and minimizes its damage to the environment. Therefore, it is of great theoretical and practical significance to carry out the preparation and catalytic performance research of metal-modified carbon-based solid acid catalysts.
[0008] Based on this, the present application provides a metal-modified carbon-based solid acid catalyst and its preparation method and application. The catalyst is used to catalyze the synthesis of acetal (ketone) fragrances. It has good catalytic performance, low production cost, green environmental protection, simple recycling and good repeatability, and realizes waste utilization of resources.
[0009] A method for preparing a metal-modified carbon-based solid acid catalyst comprises:
[0010] (1) dissolving waste cooking oil, metal salt and phase transfer agent in an ethanol aqueous solution to obtain a reaction mixture;
[0011] (2) subjecting the reaction mixture to ultrasound, magnetic stirring, and oil bath heating and stirring treatments in sequence to obtain a catalyst precursor;
[0012] (3) calcining the obtained catalyst precursor in a nitrogen atmosphere to obtain a metal-modified carbon-based solid acid catalyst.
[0013] Carbon-based solid acids have shown significant advantages in the field of catalysis due to their high specific surface area and thermal stability. Such catalysts can effectively promote specific chemical reactions while reducing the occurrence of side reactions. With the development of green chemistry, the preparation of carbon-based solid acids using waste materials or biomass as raw materials has become a new research direction. This application designs a metal-modified carbon-based solid acid catalyst for a series of reaction conditions and post-processing problems in the acetal (ketone) reaction process.
[0014] The present application uses waste cooking oil as a raw material as a carbon material, and through a series of pretreatments such as ultrasound, phase transfer agent, and heating and stirring, the metal is loaded on the carbon material, and then calcined at about 500°C and nitrogen for about 2 hours to obtain a metal-modified carbon-based solid acid catalyst. The present application improves the pretreatment process, so that the activity of the catalyst prepared by using waste cooking oil as a carbon material is basically unaffected, and the activity of the catalyst prepared by using pure oil as a carbon material is even better.
[0015] The rich hierarchical porous structure of the waste catering oil carbon material can reduce the mass transfer resistance, and the high specific surface area can expose more active sites to enhance its catalytic activity; the dispersion system is made more stable by adding a phase transfer agent, and the mixing of the entire reaction system is accelerated by ultrasound. These two pretreatment steps can make the metal salts better adhere to the waste catering oil carbon material, so that the catalytic activity and stability of the catalyst prepared by the present invention are significantly improved, the yield of catalytic preparation of acetal / ketal flavors is above 90%, the purity of the product is above 98%, and the catalyst can be recycled. After repeating the experiment 5 times, the yield fluctuation is measured to be within 5%.
[0016] Several optional methods are also provided below, but they are not intended to be additional limitations on the above-mentioned overall solution, but are merely further supplements or preferences. Under the premise that there are no technical or logical contradictions, each optional method can be combined with the above-mentioned overall solution separately, and multiple optional methods can also be combined.
[0017] In step (1):
[0018] Optionally, the metal salt is one of the hydrochlorides, nitrates or acetates of tin (II), tin (IV), iron, zirconium, zinc, copper, manganese, nickel, chromium, samarium and lanthanum.
[0019] Further optionally, the metal salt is ferric chloride, stannous chloride, zirconium chloride; more preferably, the metal salt is ferric chloride or zirconium chloride; most preferably, the metal salt is zirconium chloride. The catalytic yield of C-Zr, C-Sn(II), and C-Fe can reach more than 85%, the catalytic yield of C-Zr and C-Fe can reach more than 90%, and the catalytic yield of C-Zr can reach 96%.
[0020] Optionally, the phase transfer agent is any one of hexadecyltrimethylammonium chloride, benzyltriethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride, and crown ether.
[0021] Further optionally, the phase transfer agent is tetrabutylammonium bromide or tetrabutylammonium chloride.
[0022] The most preferred combination is that the metal salt is zirconium chloride and the phase transfer agent is tetrabutylammonium bromide.
[0023] Optionally, the amount of waste catering oil is based on 20 g, the amount of metal salt is 0.02 mol to 0.04 mol, the mass of the phase transfer agent is 0.2 to 0.6 g, and the volume of the ethanol aqueous solution is 80 to 120 mL.
[0024] Further optionally, the amount of the metal salt is 0.03 mol to 0.04 mol. Under this amount condition, the catalytic yield can reach more than 96%.
[0025] Further optionally, the amount of waste catering oil is based on 20 g, the amount of metal salt is 0.03 mol, and the mass of the phase transfer agent is 0.4 g.
[0026] Optionally, the ethanol aqueous solution is an ethanol aqueous solution with a volume percentage of 30% to 75%.
[0027] Further optionally, the volume ratio of ethanol in the ethanol aqueous solution is 55%; the volume of the ethanol aqueous solution is 100 mL.
[0028] In step (2):
[0029] Optionally, the ultrasonic time is 0.5h to 1.5h.
[0030] Optionally, the magnetic stirring time is 1 to 3 hours; the oil bath temperature is 90 to 110° C., and the oil bath time is 6 to 12 hours.
[0031] Optionally, the ultrasonic time is 1 hour; the magnetic stirring time is 2 hours; the oil bath stirring temperature is 100° C., and the time is 10 hours;
[0032] In step (3):
[0033] Optionally, the calcination temperature is 300-700° C., the calcination time is 1-3 hours, and the heating rate is 5-15° C. / min.
[0034] Further optionally, the calcination temperature in the tubular furnace is 500° C., the calcination time is 2 h, and the heating rate is 10° C. / min.
[0035] In the present application, the catalytic activity of the catalyst prepared by optimizing the above-mentioned waste oil, metal zirconium chloride and ratio is significantly improved, and the amount of catalyst used in the catalytic reaction is reduced; after the reaction is completed, the catalyst is easy to recover and reuse, the catalytic activity is stable, and the catalytic effect remains good.
[0036] The most preferred preparation method is:
[0037] Based on 20g of waste catering oil, the metal salt is zirconium chloride, and the amount of substance is 0.03mol; the phase transfer agent is tetrabutylammonium bromide, and the mass is 0.4g; the volume ratio of ethanol in the ethanol aqueous solution is 55%; the ultrasonic time is 1h; the magnetic stirring time is 2h; the oil bath stirring temperature is 100°C, and the time is 10h; the tubular furnace calcination temperature is 500°C, the calcination time is 2h, and the heating rate is 10°C / min.
[0038] The present application also provides a metal-modified carbon-based solid acid catalyst prepared by the preparation method.
[0039] The present application also provides an application of the metal-modified carbon-based solid acid catalyst in the preparation of acetal (ketone).
[0040] The present application also provides a method for preparing acetal (ketone) fragrance, comprising:
[0041] (1) using aldehyde / ketone and alcohol as raw materials, cyclohexane as a water-carrying agent, and the metal-modified carbon-based solid acid catalyst as a catalyst, and conducting an oil bath reaction;
[0042] (2) After the reaction is completed, the reaction system is cooled until the temperature drops below 50°C, the upper liquid is separated, and the upper liquid is washed with sodium hydroxide solution, semi-saturated brine and water in sequence, and the fraction of 224-228°C is collected by atmospheric distillation to obtain the product.
[0043] Optionally, the amount of the metal-modified carbon-based solid acid catalyst is 1% to 3% of the mass of the aldehyde / ketone. Further optionally, the amount of the metal-modified carbon-based solid acid catalyst is 2% to 3% of the mass of the aldehyde / ketone; most preferably, the amount of the metal-modified carbon-based solid acid catalyst is 2% of the mass of the aldehyde / ketone. The catalytic yield can reach more than 96% in the range of 2wt% to 3wt%, and the yield is higher and the cost is lower at 2wt%.
[0044] The acetal (ketone) refers to acetal or ketal; the aldehyde / ketone refers to aldehyde or ketone, the aldehyde is benzaldehyde, phenylacetaldehyde or cinnamaldehyde, and the ketone is cyclohexanone; the alcohol is ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol or glycerol; the molar ratio of the aldehyde (ketone) to the alcohol is 1:1-2, more preferably 1:1.6-1.8, and most preferably 1:1.6. Within the range of 1:1.6-1.8, the yield reaches more than 96%. A further preferred raw material combination is: benzaldehyde and ethylene glycol, benzaldehyde and 1,2-propylene glycol, benzaldehyde and 1,3-propylene glycol, phenylacetaldehyde and ethylene glycol, benzaldehyde and glycerol, cinnamaldehyde and ethylene glycol, cyclohexanone and ethylene glycol or cyclohexanone and 1,2-propylene glycol; the molar ratio of the two is 1:1.6-1.8.
[0045] A further preferred combination is: phenylacetaldehyde and ethylene glycol or benzaldehyde and 1,3-propylene glycol, the molar ratio of the two being 1:1.6.
[0046] Optionally, based on 0.1 mol of the raw material aldehyde, the amount of the water-carrying agent is 10-16 ml; further, it can be 10-14 ml, and most preferably 12 ml. The product yield reaches a peak when the content of the cyclohexane water-carrying agent is 12 mL.
[0047] Optionally, the mass percentage concentration of the sodium hydroxide solution used for cleaning is 5%.
[0048] Optionally, in step (1), the oil bath reaction time is 1 to 4 hours, further 3 to 3.5 hours, and the reaction time is more than 3 hours, and the catalytic yield reaches more than 96%.
[0049] The most preferred reaction is carried out in an oil bath at 110° C. for 3 hours. The yield and purity of the acetal (ketal) fragrance prepared by catalysis under the above preferred conditions can reach a higher value.
[0050] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0051] (1) The present application uses waste cooking oil as the carbon source of carbon-based solid acid and improves the way it is combined with metal salts, so that compared with similar catalysts using pure oil as the carbon source, its catalytic activity is not reduced but maintains a higher yield with less catalyst usage.
[0052] (2) The present application uses waste cooking oil as the carbon source of carbon-based solid acid, and combines the carbon-based solid acid with an acidic functional group through metal modification. The obtained metal-modified carbon-based solid acid catalyst has good catalytic performance and is applied to the preparation reaction of acetal (ketone) flavors, showing good catalytic activity; and the reaction can still maintain a high product selectivity under the premise of a low catalyst usage, greatly reducing the production cost; the prepared metal-modified carbon-based solid acid catalyst is easy to recover and recyclable after the reaction is completed, thereby maximizing the utilization efficiency of resources.
[0053] (3) The outstanding advantage of this application is that it converts waste restaurant oil, which has waste properties, into usable resources, which not only provides a new option for waste oil treatment, but also realizes waste resource utilization and improves the utilization value of waste. The catalyst prepared in this application complies with the principles of green chemistry, and the metal-modified carbon-based solid acid catalyst has the advantages of being renewable, highly efficient and having low environmental impact. Using waste restaurant oil as a loading material for the catalyst can harmlessly treat and utilize the waste restaurant oil as a resource, which complies with the concept of green, environmentally friendly and sustainable development, and minimizes its negative impact on the environment. At the same time, this application will also reduce the use of traditional catalysts and promote the development of environmental protection technology. DETAILED DESCRIPTION
[0054] The technical solution of the present application will be described clearly and completely in conjunction with the embodiments below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0056] The raw materials used in the following examples are all commercially available products.
[0057] Based on the above-mentioned method for preparing a metal-modified carbon-based solid acid catalyst, the following is described with specific examples:
[0058] The waste cooking oil used in the following examples is common waste cooking oil, and the chemical raw materials used are all commercially available products.
[0059] Example 1
[0060] Taking 20g of catering waste oil and zirconium chloride as an example, the preparation method of the catalyst is as follows:
[0061] (1) Accurately weigh 20 g of waste cooking oil, 0.03 mol of zirconium chloride and 0.4 g of tetrabutylammonium bromide into a 500 mL beaker, add 100 mL of 55% by volume ethanol aqueous solution, and place the beaker in an ultrasonic machine for 1 h at 20 W power.
[0062] (2) After ultrasonication, the sample was placed on a magnetic stirring device and stirred for 2 h. The beaker was then placed in an oil bath magnetic stirring pot at 100 °C for 10 h, and stirred thoroughly until the mixed liquid became viscous.
[0063] (3) After stirring, the viscous substance in the beaker was placed in a quartz boat and calcined in a nitrogen atmosphere tubular furnace at a heating rate of 10°C / min, a tubular furnace calcination temperature of 500°C, and a calcination time of 2h. After cooling, the catalyst was obtained, which was recorded as C-Zr solid acid catalyst.
[0064] By replacing the metal salt in the above preparation steps (the amount of substance remains unchanged), different catalysts are prepared: C-Sn(IV), C-Sn(II), C-Fe, C-Co, C-Ni, C-Cu, C-Zn, C-Mn, C-Sm, and C-La.
[0065] The different metal-modified carbon-based solid acid catalysts prepared above were used to catalyze the synthesis of acetal (ketone) fragrances in the following examples.
[0066] Example 2
[0067] Into a 100mL three-necked flask equipped with a mechanical stirring device, a water separator and a reflux condenser, 10.61g (0.1mol) of benzaldehyde, 9.93g (0.16mol) of ethylene glycol, 12mL of cyclohexane water-carrying agent and 0.21g of catalyst (prepared in Example 1) were added respectively, and then stirred in a 110°C oil bath for reaction for 3h. After the reaction, the reaction system was cooled to room temperature. When the temperature dropped below 50°C, the supernatant was separated, and the supernatant was washed with 5wt% sodium hydroxide solution, semi-saturated brine and water in turn, and then the 224-228°C fraction was collected by atmospheric distillation to obtain a colorless transparent liquid with fruity aroma, which was the product benzaldehyde ethylene glycol acetal. The purity of the reaction product was analyzed by gas chromatography.
[0068] The results obtained by catalyzing the acetalization reaction with different metal-modified carbon-based solid acid catalysts are shown in Table 1.
[0069] Table 1 Acetalization reaction results of different metal modified carbon-based solid acid catalysts
[0070] Catalyst type Yield / % purity / % C-Zr 96.0 99.3 C-Sn(IV) 70.5 98.8 C-Sn(II) 85.6 99.1 C-Fe 93.8 98.9 C-Co 78.5 99.3 C-Ni 80.6 99.2 C-Cu 81.5 99.2 C-Zn 75.9 99.1 C-Mn 80.1 99.2 C-Sm 76.1 98.8 C-La 82.1 98.7
[0071] It can be seen from the results in Table 1 that the yields of the different catalysts prepared in Example 1 for catalyzing the benzaldehyde ethylene glycol acetal reaction can reach more than 70%, among which the catalytic yields of C-Zr, C-Sn(II) and C-Fe can reach more than 85%, the catalytic yields of C-Zr and C-Fe can reach more than 90%, and the catalytic yield of C-Zr can reach 96%.
[0072] Example 3
[0073] This example is based on the experimental results obtained in Example 2. On the basis of the conclusion that the catalyst with better catalytic effect is C-Zr, the catalytic performance of the carbon-based solid acid catalyst modified with different loading amounts of metal zirconium is further verified.
[0074] The steps for preparing the metal-modified carbon-based solid acid catalyst are the same as those in Example 1. When other conditions remain unchanged, the content of zirconium chloride in the reaction system is changed (0.005 mol, 0.01 mol, 0.02 mol, 0.03 mol, 0.04 mol), and metal zirconium-modified carbon-based solid acid catalysts with different loading amounts can be prepared, which are marked as C-Zr(25), C-Zr(50), C-Zr(100), C-Zr(150), and C-Zr(200), respectively.
[0075] Into a 100mL three-necked flask equipped with a mechanical stirring device, a water separator and a reflux condenser, 10.61g (0.1mol) of benzaldehyde, 9.93g (0.16mol) of ethylene glycol, 12mL of cyclohexane water-carrying agent and 0.21g of C-Zr series catalyst were respectively added, and then stirred in a 110°C oil bath for reaction for 3h. After the reaction, the reaction system was cooled to room temperature. When the temperature dropped below 50°C, the upper liquid was separated, and the upper liquid was washed with sodium hydroxide solution, semi-saturated brine and water in turn, and then the 224-228°C fraction was collected by atmospheric distillation to obtain a colorless transparent liquid with fruity aroma, which was the product benzaldehyde ethylene glycol acetal. The purity of the reaction product was analyzed by gas chromatography.
[0076] The results obtained by catalyzing the acetalization reaction with different loading amounts of metal zirconium modified carbon-based solid acid catalysts are shown in Table 2.
[0077] Table 2 Results of acetalization reaction using metal zirconium modified carbon-based solid acid catalysts with different loading amounts
[0078] Catalyst type Yield / % purity / % C-Zr(25) 76.6 98.9 C-Zr(50) 80.5 98.8 C-Zr(100) 87.2 99.1 C-Zr(150) 96.0 99.3 C-Zr(200) 96.1 98.9
[0079] From the results in Table 2, it can be seen that when the loading amount of metal zirconium is 0.03 mol / 0.04 mol, the yield of the benzaldehyde glycol acetal reaction product is relatively high, reaching more than 96%, indicating that the catalyst has good catalytic activity. There is no obvious difference in the yields of the two. Under the condition of similar catalytic results, the overall cost of the catalyst product with a loading amount of 0.03 mol is lower.
[0080] Example 4
[0081] Into a 100mL three-necked flask equipped with a mechanical stirring device, a water separator and a reflux condenser, 10.61g (0.1mol) of benzaldehyde, different amounts of ethylene glycol, 12mL of cyclohexane water-carrying agent and 0.21g of C-Zr (150) catalyst (prepared in Example 3) were respectively added, and then stirred in an oil bath at 110°C for 3h. After the reaction, the reaction system was cooled to room temperature. When the temperature dropped below 50°C, the supernatant was separated, and the supernatant was washed with sodium hydroxide solution, semi-saturated brine and water in turn, and then the 224-228°C fraction was collected by atmospheric distillation to obtain a colorless transparent liquid with fruity aroma, which was the product benzaldehyde ethylene glycol acetal. The purity of the reaction product was analyzed by gas chromatography.
[0082] The acetal reaction results obtained by changing the molar ratio of benzaldehyde to ethylene glycol are shown in Table 3
[0083] Table 3 Acetal preparation results at different molar ratios of benzaldehyde and ethylene glycol
[0084] Aldehyde-alcohol ratio Yield / % purity / % 1:1.2 81.9 98.9 1:1.4 89.2 99.1 1:1.6 96.0 99.3 1:1.8 96.3 99.4 1:2.0 90.5 98.8
[0085] From the results in Table 3, it can be seen that with the increase of the molar ratio of aldehyde to alcohol, the yield of benzaldehyde glycol acetal also gradually increases. When the molar ratio of aldehyde to alcohol is 1:1.6, the yield reaches 96%. The subsequent increase in the alcohol content does not significantly increase the yield and even shows a downward trend. Therefore, the optimal aldehyde-alcohol ratio is 1:1.6.
[0086] Example 5
[0087] Into a 100mL three-necked flask equipped with a mechanical stirring device, a water separator and a reflux condenser, 10.61g (0.1mol) of benzaldehyde, 9.93g (0.16mol) of ethylene glycol, 12mL of cyclohexane water-carrying agent and different amounts of C-Zr (150) catalyst (prepared in Example 3) were respectively added, and then stirred in an oil bath at 110°C for 3h. After the reaction, the reaction system was cooled to room temperature. When the temperature dropped below 50°C, the supernatant was separated, and the supernatant was washed with sodium hydroxide solution, semi-saturated brine and water in turn, and then the 224-228°C fraction was collected by atmospheric distillation to obtain a colorless transparent liquid with fruity aroma, which was the product benzaldehyde ethylene glycol acetal. The purity of the reaction product was analyzed by gas chromatography.
[0088] The results of the acetalization reaction obtained by changing the amount of catalyst are shown in Table 4.
[0089] Table 4 Acetal preparation results with different catalyst amounts
[0090] Catalyst amount / wt% Yield / % purity / % 1.0 88.9 98.8 1.5 92.4 99.4 2.0 96.0 99.3 2.5 96.5 98.9 3.0 97.2 98.9
[0091] From the results in Table 4, it can be seen that when the catalyst amount is 2 wt%, the yield is higher and the cost is lower.
[0092] Example 6
[0093] Into a 100mL three-necked flask equipped with a mechanical stirring device, a water separator and a reflux condenser, 10.61g (0.1mol) of benzaldehyde, 9.93g (0.16mol) of ethylene glycol, 12mL of cyclohexane water-carrying agent and 0.21g of C-Zr (150) (prepared in Example 3) catalyst were respectively added, and then stirred in a 110°C oil bath for reaction for different times. After the reaction, the reaction system was cooled to room temperature. When the temperature dropped to below 50°C, the supernatant was separated, and the supernatant was washed with sodium hydroxide solution, semi-saturated brine and water in turn, and then the 224-228°C fraction was collected by atmospheric distillation to obtain a colorless transparent liquid with fruity aroma, which was the product benzaldehyde ethylene glycol acetal. The purity of the reaction product was analyzed by gas chromatography.
[0094] The acetal reaction results obtained by changing the reaction time are shown in Table 5.
[0095] Table 5 Acetal preparation results at different reaction times
[0096]
[0097]
[0098] From the results in Table 5, it can be seen that when the reaction time is more than 3 h, the product yield is significantly improved compared with before. When it exceeds 3 h, the yield tends to be stable without obvious improvement. Therefore, the optimal reaction time is 3 h.
[0099] Example 7
[0100] Into a 100mL three-necked flask equipped with a mechanical stirring device, a water separator and a reflux condenser, 10.61g (0.1mol) of benzaldehyde, 9.93g (0.16mol) of ethylene glycol, different amounts of cyclohexane water-carrying agent and 0.21g of C-Zr (150) catalyst (prepared in Example 3) were added respectively, and then stirred in an oil bath at 110°C for 3h. After the reaction, the reaction system was cooled to room temperature. When the temperature dropped below 50°C, the supernatant was separated, and the supernatant was washed with sodium hydroxide solution, semi-saturated brine and water in turn, and then the 224-228°C fraction was collected by atmospheric distillation to obtain a colorless transparent liquid with fruity aroma, which was the product benzaldehyde ethylene glycol acetal. The purity of the reaction product was analyzed by gas chromatography.
[0101] The results of the acetal reaction obtained by changing the water dosage are shown in Table 6.
[0102] Table 6 Results of acetal preparation with different water dosages
[0103] Dose with water / ml Yield / % purity / % 8 82.1 99.2 10 90.9 98.8 12 96.0 99.3 14 96.4 98.9 16 93.5 99.2
[0104] From the results in Table 6, it can be seen that the product yield reaches a peak value when the cyclohexane water-carrying agent content is 12 mL.
[0105] Example 8
[0106] Into a 100mL three-necked flask equipped with a mechanical stirring device, a water separator and a reflux condenser, 10.61g (0.1mol) of benzaldehyde, 9.93g (0.16mol) of ethylene glycol, 12mL of cyclohexane water-carrying agent, and 0.21g of newly prepared C-Zr (150) catalyst and C-Zr (150) catalyst that has been reused several times were added respectively, and then stirred in a 110°C oil bath for reaction for 3h. After the reaction, the reaction system was cooled to room temperature. When the temperature dropped below 50°C, the supernatant was separated, and the supernatant was washed with 5% sodium hydroxide solution, semi-saturated brine and water in turn, and then the 224-228°C fraction was collected by atmospheric distillation to obtain a colorless transparent liquid with fruity aroma, which was the product benzaldehyde ethylene glycol acetal. The purity of the reaction product was analyzed by gas chromatography.
[0107] The acetalization results of the new and old catalysts are shown in Table 7.
[0108] Table 7 Acetal reaction results of new and old catalysts
[0109]
[0110]
[0111] It can be seen from Table 7 that the C-Zr(150) catalyst has good stability. After being reused 5 times, the yield of catalytic preparation of acetal / ketal fragrances is still above 90%, and the purity of the product is above 98%.
[0112] Comparative Example 1
[0113] In a 100 mL three-necked flask equipped with a mechanical stirring device, a water separator and a reflux condenser, 10.61 g (0.1 mol) of benzaldehyde, 9.93 g (0.16 mol) of ethylene glycol, 12 mL of cyclohexane water agent, and 0.21 g of C-Zr (150) catalyst (prepared in Example 3) and C-Zr (150) without adding a phase transfer agent during the preparation process (the rest of the steps are consistent with Example 1) were added respectively. * Catalyst, then stirred in an oil bath at 110°C for 3 hours. After the reaction, the reaction system was cooled to room temperature. When the temperature dropped below 50°C, the supernatant was separated and washed with 5% sodium hydroxide solution, semi-saturated brine and water in turn. Then, the 224-228°C fraction was collected by atmospheric distillation to obtain a colorless transparent liquid with fruity aroma, which was the product benzaldehyde ethylene glycol acetal. The purity of the reaction product was analyzed by gas chromatography.
[0114] Table 8 Effect of phase transfer agent on catalytic performance of catalyst
[0115] Catalyst type Yield / % purity / % C-Zr(150) 96.0 99.3 <![CDATA[C-Zr(150) * ]]> 80.0 99.1
[0116] Comparative Example 2
[0117] In a 100 mL three-necked flask equipped with a mechanical stirring device, a water separator and a reflux condenser, 10.61 g (0.1 mol) of benzaldehyde, 9.93 g (0.16 mol) of ethylene glycol, 12 mL of cyclohexane water agent and 0.21 g of C-Zr (150) catalyst (prepared in Example 3) and C-Zr (150) without ultrasound during the preparation process (the rest of the steps are consistent with Example 1) were added respectively. *Catalyst, then stirred in an oil bath at 110°C for 3 hours. After the reaction, the reaction system was cooled to room temperature. When the temperature dropped below 50°C, the supernatant was separated and washed with 5% sodium hydroxide solution, semi-saturated brine and water in turn. Then, the 224-228°C fraction was collected by atmospheric distillation to obtain a colorless transparent liquid with fruity aroma, which was the product benzaldehyde ethylene glycol acetal. The purity of the reaction product was analyzed by gas chromatography.
[0118] Table 9 Effect of ultrasound on catalytic performance of catalyst
[0119] Catalyst type Yield / % purity / % C-Zr(150) 96.0 99.3 <![CDATA[C-Zr(150) * ]]> 77.1 98.4
[0120] Comparative Example 3
[0121] In a 100 mL three-necked flask equipped with a mechanical stirring device, a water separator and a reflux condenser, 10.61 g (0.1 mol) of benzaldehyde, 9.93 g (0.16 mol) of ethylene glycol, 12 mL of cyclohexane water agent, and 0.21 g of C-Zr (150) catalyst (prepared in Example 3) and C-Zr (150) without ultrasound or phase transfer agent (the rest of the steps are the same as in Example 1) were added respectively. * Catalyst, then stirred in an oil bath at 110°C for 3 hours. After the reaction, the reaction system was cooled to room temperature. When the temperature dropped below 50°C, the supernatant was separated and washed with 5% sodium hydroxide solution, semi-saturated brine and water in turn. Then, the 224-228°C fraction was collected by atmospheric distillation to obtain a colorless transparent liquid with fruity aroma, which was the product benzaldehyde ethylene glycol acetal. The purity of the reaction product was analyzed by gas chromatography.
[0122] Table 10 Effects of ultrasound and phase transfer agent on the catalytic performance of catalysts
[0123] Catalyst type Yield / % purity / % C-Zr(150) 96.0 99.3 <![CDATA[C-Zr(150) * ]]> 62.9 95.6
[0124] Comparative Example 4
[0125] In a 100 mL three-necked flask equipped with a mechanical stirring device, a water separator and a reflux condenser, 10.61 g (0.1 mol) of benzaldehyde, 9.93 g (0.16 mol) of ethylene glycol, 12 mL of cyclohexane with water, and 0.21 g of C-Zr (150) catalyst (prepared in Example 3) and C-Zr (150) prepared using fresh vegetable oil as a carbon source without ultrasound or addition of a phase transfer agent (the remaining steps are consistent with Example 1) were added respectively. aCatalyst, then stirred in an oil bath at 110°C for 3 hours. After the reaction, the reaction system was cooled to room temperature. When the temperature dropped below 50°C, the supernatant was separated and washed with 5% sodium hydroxide solution, semi-saturated brine and water in turn. Then, the 224-228°C fraction was collected by atmospheric distillation to obtain a colorless transparent liquid with fruity aroma, which was the product benzaldehyde ethylene glycol acetal. The purity of the reaction product was analyzed by gas chromatography.
[0126] Table 10 Effects of ultrasound and phase transfer agent on the catalytic performance of catalysts
[0127] Catalyst type Yield / % purity / % C-Zr(150) 96.0 99.3 <![CDATA[C-Zr(150) a ]]> 96.7 99.5
[0128] It can be seen from the comparison of the above comparative examples 1 to 4 that when waste oil is used as a carbon source, the synergistic effect of adding a phase transfer agent and ultrasound can effectively solve the problem that when waste oil is used as a carbon source, the metal salt cannot be effectively loaded, resulting in reduced activity.
[0129] The results of the above embodiments and comparative examples show that the catalyst prepared in the present application shows good catalytic activity and high product selectivity when a lower catalyst usage amount is used, and the post-treatment is simple and less polluting, which belongs to green chemical technology.
[0130] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A method for preparing a metal-modified carbon-based solid acid catalyst, characterized in that: include: (1) dissolving waste cooking oil, metal salt and phase transfer agent in an ethanol aqueous solution to obtain a reaction mixture; (2) subjecting the reaction mixture to ultrasound, magnetic stirring, and oil bath heating and stirring treatments in sequence to obtain a catalyst precursor; (3) calcining the obtained catalyst precursor in a nitrogen atmosphere to obtain a metal-modified carbon-based solid acid catalyst.
2. The preparation method according to claim 1, characterized in that: In step (1), the metal salt is one of the hydrochlorides, nitrates or acetates of tin (II), tin (IV), iron, zirconium, zinc, copper, manganese, nickel, chromium, samarium and lanthanum.
3. The preparation method according to claim 1, characterized in that: In step (1), the phase transfer agent is any one of hexadecyltrimethylammonium chloride, benzyltriethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride and crown ether.
4. The preparation method according to claim 1, characterized in that: In step (1), the amount of waste cooking oil is based on 20 g, the amount of the metal salt is 0.02 mol to 0.04 mol, the mass of the phase transfer agent is 0.2 to 0.6 g, and the volume of the ethanol aqueous solution is 80 to 120 mL.
5. The preparation method according to claim 1, characterized in that: In step (2): the ultrasonic time is 0.5h to 1.5h.
6. The preparation method according to claim 1, characterized in that: In step (2), the magnetic stirring time is 1 to 3 hours; the oil bath temperature is 90 to 110° C., and the oil bath time is 6 to 12 hours.
7. The preparation method according to claim 1, characterized in that: In step (3), the calcination temperature is 300-700° C., the calcination time is 1-3 hours, and the heating rate is 5-15° C. / min.
8. A metal-modified carbon-based solid acid catalyst prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the metal-modified carbon-based solid acid catalyst as claimed in claim 8 in the preparation of acetal (ketone).
10. A method for preparing acetal (ketone) fragrance, characterized in that: include: (1) using aldehyde / ketone and alcohol as raw materials, cyclohexane as a water-carrying agent, and the metal-modified carbon-based solid acid catalyst as claimed in claim 8 as a catalyst, and conducting an oil bath reaction; (2) After the reaction is completed, the reaction system is cooled until the temperature drops below 50°C, the upper liquid is separated, and the upper liquid is washed with sodium hydroxide solution, semi-saturated brine and water in sequence, and the fraction of 224-228°C is collected by atmospheric distillation to obtain the product.
Citation Information
Patent Citations
Preparation method of porous polyvinyl acetal / ketone
CN108822236A